Direct Production of (R)‐3‐Hydroxybutyric Acid of High Optical Purity by Halomonas sp. OITC1261 Under Aerobic conditions. Issue 2 (30th October 2017) - Yokaryo, Hiroto; Teruya, Morimi; Hanashiro, Ryuji; Goda, Masahiro; Tokiwa, Yutaka
Abstract : The chiral compound ( R )‐3‐hydroxybutyric acid ( R ‐3HB) has some important physiological functions in the human body and can also be applied as a functional material for industrial products. A novel Halomonas sp. OITC1261 isolated from a coastal sediment is selected for efficient production of R ‐3HB. This strain secreted R ‐3HB of high optical purity into the extracellular medium while maintaining poly(3‐hydroxybutyric acid) (PHB) inside the microbial cell under aerobic conditions. There is a possibility that R ‐3HB is generated independently of PHB. Under aerobic cultivation, 58 g L −1 (0.65 g L −1 h −1 ) of R ‐3HB was produced simultaneously with 27 g L −1 (0.30 g L −1 h −1 ) of PHB. This direct production method of R ‐3HB contributes to the improvement of mass production technology. Abstract : Holomonas sp. OITC1261 simultaneously produced (R)‐3‐hydroxybutyric acid (R‐3HB; 58 g L −1 ) and PHB (27 g L −1 ). R‐3HB is produced and secreted into medium without the hydrolysis process of PHB. This level is one of the highest production of R‐3HB by aerobic culture to date.